Public relations and strategic communication in 2050 : trends shaping the future of the profession - Laskin, Alexander V.; Freberg, Karen June (New York, NY : Routledge, 2025)
"Taking stock of the technological, political, economic, and social trends that exist today, this book extends the discussion to analyze and predict how these trends will affect the public relations and strategic communication industry of the future. The book is divided into two sections, the first addressing such key topics as artificial intelligence (AI), big data, political polarization, and misinformation, the second looking at key facets of the profession, such as media relations, crisis communication, and measurement and evaluation. Leading researchers in the discipline share their analysis of these topics while also providing theoretically based and practically relevant insights on how the industry must evolve to keep up with, and perhaps anticipate, changes in culture, society, and technology. This book will be of interest to scholars, industry professionals, and advanced undergraduate and graduate students in public relations and strategic communication"--
Keywords: Public relations; LANGUAGE ARTS & DISCIPLINES / Communication; BUSINESS & ECONOMICS / Public Relations